Decolonising Political Communication in Africa - Karam, Beschara; Mutsvairo, Bruce (2021)
This book uses decolonisation as a lens to interrogate political communication styles, performance, and practice in Africa and the diaspora. The book interrogates the theory and practice of political communication, using decolonial research methods to begin a process of self-reflexivity and the creation of a new approach to knowledge production about African political communication. In doing so, it explores political communication approaches that might until recently have been considered subversive or dissident: forms of political communication that served to challenge imposed western norms and to empower African citizens and their histories. Centring African scholarship, the book draws on case studies from across the continent, including Zimbabwe, South Africa, Nigeria and Ghana. This book will be of interest to students and scholars of politics, media and communication in Africa.